How to develop and implement a national drug policy. (World Health Organization, 2001)
In Europe today, HIV/AIDS prevention, treatment and care are needed more than ever. HIV incidence steady in western and central Europe, and dramatically increasing in eastern Europe remains a major challenge to public health in the 21st century. With more than two million people living with HIV/AIDS in the WHO European Region, no country has been spared. This book tells the story of HIV/AIDS in Europe from a broad variety of perspectives: biomedical, social, cultural, economic and political. The authors are leading experts from across the Region and include both the infected and the affected.